BUILDING A DYNAMIC CROPPING TREND VISUALIZATION SOFTWARE TO ASSESS FARMING PROGRESSIVENESS - MANNAN, MUHAMMAD ABDUL; AL MAMUN, MD. MUNTASEER; LEMON, MD. NAZIUR ISLAM; SIMA, SHAMMI AKTER; RAHMAN, MD. ASHIKUR; TASNIM, MAHRUPA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
This thesis presents a comprehensive study that unfolds in two key dimensions. Firstly, a novel cropping trend visualization software was developed, aiming to provide a dynamic and insightful tool for assessing farming progressiveness. This software, a product of meticulous design and implementation, serves as an innovative instrument for visualizing and analyzing cropping trends in agriculture. In the second part of the study, the software was utilized to gather descriptive and inferential statistical data from a sample of 111 farmers. The data analysis reveals noteworthy correlations between specific agricultural practices and farming progressiveness. Key findings indicate significant positive associations between technology adoption, climate adaptation, crop variety diversity, and environmentally sustainable practices with higher levels of farming progressiveness. While certain trends exhibit statistical significance, caution is advised in drawing robust conclusions for factors with limited statistical support. These empirical insights provide a valuable foundation for policymakers, agricultural extension services, and stakeholders to strategically promote practices that enhance the overall progressiveness of farmers. The dual contribution of the developed software and the derived insights from its application underscores the significance of integrating technology in advancing sustainable and progressive agricultural practices.